Updating Climate Beliefs Based on Latest IPCC Report Points to Increased Willingness to Act - Mark Freeman; Ben Groom; Frikk Nesje; Gernot Wagner (CESifo GmbH, 2025)
We assess how changes in the scientific consensus around equilibrium climate sensitivity (ECS), as captured by the IPCC's Fifth (AR5) and Sixth (AR6) Assessment Reports, impact policymakers' willingness to take climate action. Taking the IPCC's reports at face value, the ECS estimates in AR6 would have lowered a policymaker's willingness to act on climate relative to AR5 due to a narrower "likely" range. However, Bayesian updating may reverse this conclusion. An accuracy-motivated policymaker who was not convinced to take greater climate action by the evidence in AR5 may be more likely to strengthen their policy views by the evidence in AR6.
Keywords: Q54; H51; D83; 330; equilibrium climate sensitivity; Bayesian updating; climate policy